2018
DOI: 10.1523/jneurosci.3489-17.2018
|View full text |Cite
|
Sign up to set email alerts
|

Identification of a Rhythmic Firing Pattern in the Enteric Nervous System That Generates Rhythmic Electrical Activity in Smooth Muscle

Abstract: The enteric nervous system (ENS) contains millions of neurons essential for organization of motor behavior of the intestine. It is well established that the large intestine requires ENS activity to drive propulsive motor behaviors. However, the firing pattern of the ENS underlying propagating neurogenic contractions of the large intestine remains unknown. To identify this, we used high-resolution neuronal imaging with electrophysiology from neighboring smooth muscle. Myoelectric activity underlying propagating… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
64
0
1

Year Published

2019
2019
2022
2022

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 71 publications
(69 citation statements)
references
References 53 publications
4
64
0
1
Order By: Relevance
“…We found no direct studies of Akt activation by depolarization in enteric neurons, however, and the relevance of depolarization frequency for GI motility has not been reported. Recent work examining myenteric plexus Ca 2+ waves suggests a wide depolarization frequency range (0.2 to 1.3 Hz) for nitrergic neurons that overlaps the 0.25 to 0.5 Hz EFS at which we saw Akt inhibitor effects (16). Importantly, our results show that Akt-dependent nNOS S1412 augmentation of nitrergic relaxation is detected only when intracellular [Ca 2+ ] is expected to be low.…”
Section: Discussionsupporting
confidence: 60%
See 2 more Smart Citations
“…We found no direct studies of Akt activation by depolarization in enteric neurons, however, and the relevance of depolarization frequency for GI motility has not been reported. Recent work examining myenteric plexus Ca 2+ waves suggests a wide depolarization frequency range (0.2 to 1.3 Hz) for nitrergic neurons that overlaps the 0.25 to 0.5 Hz EFS at which we saw Akt inhibitor effects (16). Importantly, our results show that Akt-dependent nNOS S1412 augmentation of nitrergic relaxation is detected only when intracellular [Ca 2+ ] is expected to be low.…”
Section: Discussionsupporting
confidence: 60%
“…nNOS S1412 phosphorylation may sustain NO synthesis beyond the brief depolarization of neurons (16,17), but S1412 does not appear relevant at saturating [Ca 2+ ] during high-frequency depolarization (51). nNOS S1412 tunes increased NO production to low resting [Ca 2+ ], thereby integrating several cellular signals.…”
Section: Distance (Mm)mentioning
confidence: 99%
See 1 more Smart Citation
“…Anatomisch findet sich eine Zweiteilung in den Plexus submucosus und den Plexus myentericus, der maßgeblich die Aktivität der Muskulatur steuert. Die Kommunikation zwischen enterischen Nervenzellen wird durch Interneurone sichergestellt, die Millionen von synaptischen Verbindungen im ENS aufrechterhalten [20]. Diese synaptischen Verbindungen ermöglichen sowohl die Initiierung vorwärts als auch rückwärts gerichteter Peristaltik.…”
Section: Avoiding Clustering and Urge In Transanal Surgery For Deep Dunclassified
“…We recently showed that low frequency depolarization relaxes mouse ileum via Akt phosphorylation of nNOS S1412 (D.D. Guerra et al, ); this may explain why NO responses are tuned to depolarization frequency in the gut (Spencer et al, ) and why nitrergic inhibitory junction potentials (IJPs) have a longer duration than action potentials (Hurt et al, ; Keef et al, ).…”
Section: Introductionmentioning
confidence: 99%